Parent-Child Attachment and Romantic Relationship among Young Adults in Malaysia - Fatahyah, Yahya; Sharon, Wilson; Sochos, Antigonos; Ahmad Tarmizi, Talib; Sarjit Singh, Darshan Singh; Muhammad Jazlan, Ahmad Khiri; Aqeel, Khan (Turkbilmat Egitim Hizmetleri, 2021)
The aim of this research was to examine the relationship between Parent- Child Attachment on Romantic Relationship among Young Adults in Malaysia. In the present study, researcher established the correlation between the two variables which are Parent-child attachment and romantic relationship. Total of 100 participants (36= Male; 64: Female) participated in this study. Two (2) instruments have been used to measure the variables; Armsden and Greenberg’s Inventory of Parent and Peer Attachment (IPPA) and Experiences in Close Relationships scale (ECR). Results indicated that there was a positive moderate significant relationship between parent child attachment and romantic relationship among young adults in Malaysia (r=.322, p<0.01). As a recommendation, a semi-structured interview can be administered to investigate the nature of attachment relationships in adult partnerships.